Custom NIR Imaging of New Up‐Conversion Multimodal Gadolinium Oxysulfide Nanoparticles. (18th March 2021) - Santelli, Julien; Lepoix, Carole; Lechevallier, Séverine; Martinez, Cyril; Calise, Denis; Zou, Qilin; Moyano, Sebastien; Cussac, Daniel; Verelst, Marc; Mauricot, Robert
Abstract: Up‐conversion (UC) nanoparticles (NPs) appear as promising probes for easy, cost‐effective, and efficient in vivo imaging. In this paper, a new kind of UCNPs is proposed: Gd2 O2 S:Yb 3+ /Tm 3+ for multimodal bioimaging, exhibiting a strong fluorescent emission in the near‐infrared range (802 nm) when excited at 980 nm. The in vivo fluorescence detection of such NPs is made possible by the development of a dedicated custom‐made imaging system. However, the high sensitivity of the techniques is counterbalanced with a limited resolution which highlights the necessity of combining different approaches to gather as much vital information as possible. The presence of a large amount of gadolinium also confers interesting contrasting properties both in magnetic resonance imaging (MRI) and computed tomography (CT) that could be advantageously exploited in the context of multimodal in vivo imaging. In this study, the UC emission properties and energy transfer processes of this new nanoprobe are reported. The detectability of the UCNPs is exhibited using the custom‐made imaging system in different tissues (skin, muscle, kidney, liver, brain), depths (different anatomical localization), and species (rat and mouse), punctually and chronically. Last, promising multimodal bioimaging results are presented in UC, MRI, and CT, showing a relatively low detection threshold. Abstract : In this study, a new kind of up‐conversion nanoparticles Gd2 O2 S:Yb 3+ /Tm 3+ is proposed for multimodal bioimaging, exhibiting a strong fluorescent emission in the near‐infrared range (802 nm) when excited at 980 nm. The in vivo fluorescence detection of such nanoparticles is made possible by the development of a dedicated custom‐made imaging system.